The Effect of In-situ Stress on Hydraulic Fractures Dimensions - Al Humairi, Mohammed; Abdul Hadi, Hassan (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Understanding of in-situ stress profiles and orientations plays a vital role in designing a successful hydraulic fracturing treatment. This paper is an attempet to examine the effect of lithology and in situ stress on geometery of hydraulic fractures. A hydraulic fracturing design simulator software called FracproPT with various capabilities for designing most of hydraulic fracture was used for  simulate and optimize the hydraulic fracturing. For studying purpose,  three different cases of stress gradient contrast between different formations  are considered in this study (0.4, 0.5 and 0.75 psi/ft). The results obtained from the simulator showed that  lithologies surrounding the pay zone have an effect on the fracture’s height, width, and length. Also,  Maximum height is achieved when the stress contrast between the pay zone and the surrounding layers is very small.